C-reactive Protein and Erythrocyte Sedimentation Rate Levels in Chronic Low Back Pain Patients - Dahal, Saurav; Regmi, Samikchhya; Bajracharya, Suraj; Kumar Basel, Suman; Shrestha, Shriraj; Bahadur Karki, Dhan; Maharjan, ,Basanta; Bajracharya, Aayush (Nepal Orthopaedic Association Journal, 2024)
Introduction: Lumbar disc degenerative disease, intervertebral disc herniation, lumbar stenosis, and arthritis are usual causes of chronic nonspecific low back pain. Patients with acute lumbosciatic pain usually have elevated levels of inflammatory markers such as highly sensitive C-reactive protein. However, studies that analyze the levels of Erythrocyte sedimentation rate and C-reactive proteins in patients with chronic low back pain are insufficient. Hence, this study aimed to assess the value of these markers for the determination of inflammation in patients with chronic low back pain. Method: A cross-sectional, hospital-based, observational study was conducted after receiving ethical approval from the Institutional Review Committee. The study started on Feb 20, 2023, and lasted till Aug 10, 2023. Statistical analysis of the level of inflammatory markers was done by evaluating their mean values. Results: 120 patients who presented with nonspecific chronic low back pain were evaluated clinical-radiologically and sent for blood investigations. The mean erythrocyte sedimentation rate was 11.54 mm/h, and the mean C-reactive protein level was 5.90 mg/L. Blood sedimentation rate was found to have a significant positive correlation with increasing age and female sex. Conclusion: Chronic nonspecific low back pain does not elicit a systemic inflammatory response, as evidenced by normal ESR and CRP levels.